A Note on Capital IQ's Credit Line Data. Issue 3 (August 2016) - Mathers, Ani Manakyan; Giacomini, Emanuela
Abstract: Empirical work in finance is increasingly using Capital IQ's detailed data on capital structure. We compare the Capital IQ credit line data to hand‐collected data for a random sample of firms. Missing values in Capital IQ are prevalent, so the data set underreports the importance of corporate credit lines. When data are reported, Capital IQ often differs from hand‐collected credit line activity. We suggest methods for correcting the errors in the Capital IQ data, note which portions of the data are most reliable, and quantify the effects of Capital IQ's underreporting by examining the tradeoff between cash and lines of credit.